Analytical method and apparatus for the determination of total nitrogen contents in aqueous systems - ITOH; TADAMASA; OI; NAOBUMI; YASUMASA; YOSHIAKI (1982)
An analytical method for the determination of the total nitrogen content in aqueous systems, which comprises passing an inert gas stream containing substantially no nitrogen and carbon dioxide through a reaction tube, which is packed with a decomposition catalyst and maintained at a temperature of 700 DEG to 1200 DEG C., a condenser and a moisture-absorbing tube in this order, injecting an aqueous test sample to be analyzed into the reaction tube, and sending the gaseous products coming out of the moisture-absorbing tube to a mass spectrometer to determine the nitrogen content, and an apparatus for carrying out such a method. By this method, it is possible to determine the total nitrogen content in nitrogen compounds contained in aqueous systems, rapidly, accurately and with a high sensitivity.